Alternative practices in curriculum design. Participation as a key factor and speaking out as right - Susana Barco (Universidad Politécnica Salesiana, 2012)
During the 1990s, in the context of neo-liberal policies, curricular changes ocurred in Latin América which gave a leading role to technicians and experts in education, in the process of writing the curricular documents. Beyond the critiques these policies can receive, it is necessary to find alternative ways of elaborating curricular documents, based on democratic idea of teacher's real participation.In an action-research within the scope of a university and two experiences referred to in this work, different participative styles emerged, according to their particular circumstances. This work referred to these processes and its theoretical foundations, reporting alternative ways of curricular design based on teacher's participation and its different forms. The aim is to enhance how teachers as a social subject can 'stand up for themselves'and 'speak out' in the specific practice of writing curricular documents. Taking into account that teaching practices rewrite curricular documents, different dynamics in curricular change are possible, allowing adjusting and adapting realities in each institution, and propelling collaborative work.